Witte Swaen from 1636. The Discovery and Archaeological Survey of an Intact Fluit in the Gulf of Finland, Baltic Sea - Eriksson, Niklas (The international journal of nautical archaeology, 2025)
In 2020, the diving group Badewanne discovered an exceptionally well-preserved wreck in the Gulf of Finland, Baltic Sea. Researchers and divers from several different institutions collaborated to survey the wreck with the ambition of gathering as much archaeological information with as little impact on the wreck as possible. This paper summarizes the current state of research and argues that the wreck is the remains of a merchant fluit loaded with grain. Archival research has identified the ship as Witte Swaen, built in 1636 and sunk in 1638. Besides highlighting the fate of this particular fluit, the survey has revealed the characteristic hull shape as well as the sculptural decorations, which diverge from other later archaeologically surveyed fluits in the Baltic.